Gold, Silver and Base Metal Deposits of the Chillagoe District, Australia: Hypothermal to Epithermal Overprinting (33335b9b-7938-472c-8a61-62e4b140b295) - Nethery JE (The Australasian Institute of Mining and Metallurgy, 1995)
At the Red Dome and Mungana deposits in north Queensland, Australia, it is proposed that mineralisation and alteration developed as a "telescoped" overprinting continuum, ranging in style from hypothermal to epithermal, reflecting the major changes that developed in the regional setting over the period circa 325 - 290Ma. Regional assessment suggests that this also applies to many other precious and base metal deposits within a 401an length of the host Siluro-Devonian Chillagoe Formation. A ten stage paragenetic sequence of structural preparation, multi phase intrusion and associated mineralisation, alteration and brecciation is postulated for the Chillagoe district.